2016
DOI: 10.1128/aem.02818-15
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxyR on Growth, Biofilm Formation, and Mobility of Vibrio parahaemolyticus

Abstract: Vibrio parahaemolyticus is a common marine food-borne enteropathogen. In this study, we examined the antioxidative activity, growth, biofilm formation, and cell mobility of an oxyR deletion mutant and its genetically complementary strain of V. parahaemolyticus. oxyR is the regulator of catalase and ahpC genes. Protection against extrinsic H 2 O 2 and against the organic peroxides cumene hydroperoxide and tert-butyl hydroperoxide was weaker in the deletion mutant than in its parent strain. Expression of the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…In addition, the katE mutant strain did not show reduced ability to produce biofilms, another important trait for the wilting disease development ( Figure 4 ). Biofilm-growing cells usually experience endogenous oxidative stress and many antioxidant systems were shown to be induced under this growth condition ( Resch et al, 2005 ; Ram et al, 2005 ; Mikkelsen et al, 2007 ; Shanks et al, 2007 ; Chung et al, 2016 ). In fact, the role of catalase and superoxide dismutase in the development of mature biofilms was previously demonstrated in X. citri subsp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the katE mutant strain did not show reduced ability to produce biofilms, another important trait for the wilting disease development ( Figure 4 ). Biofilm-growing cells usually experience endogenous oxidative stress and many antioxidant systems were shown to be induced under this growth condition ( Resch et al, 2005 ; Ram et al, 2005 ; Mikkelsen et al, 2007 ; Shanks et al, 2007 ; Chung et al, 2016 ). In fact, the role of catalase and superoxide dismutase in the development of mature biofilms was previously demonstrated in X. citri subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of oxyR in V. parahaemolyticus leads to a growth defect in the sugar‐rich media and impaires its biofilm formation and motility. Moreover, OxyR mediates the induction of katE (VPA1418) and aphC1 (VPA1683) by cumene . In this study, we found that loss of oxyR led to a weakened induction of katG1 and katG2 by oxidative stress, but it did not completely abolish the activation of two genes.…”
Section: Discussionmentioning
confidence: 56%
“…In V. paraheamolyticus , OxyR is required for the induction of katE1 (VPA1418) and aphC1 (VPA1683) by cumene. It is also positively associated with the growth in heated rich medium, biofilm formation and motility . RpoS plays roles in the environmental survival, acid stress resistance, and the regulation of a virulence factor PrtA .…”
Section: Introductionmentioning
confidence: 99%
“…Loss of OxyR was previously reported to affect the growth of several species of bacteria (Chung et al 2015;Maciver and Hansen 1996;Vinckx et al 2008). In our study, the growth of oxyR deletion mutants of X. oryzae pvs.…”
Section: Discussionmentioning
confidence: 63%